Gastón Gaínza: because life is a going and coming back, a meeting and getting back together - Sancho Dobles, Leonardo (2019)
This semblance reflects, from a personal perspective, on the life of Gastón Gaínza in Costa Rica. The arrival of this academic comes as a result of the putsch of 1973 in Chile, which has allowed him to develop a valuable work that has marked several generations. The author of the text gathers his experience from the teacher's hand. Recived: 05-25-2019 Approved: 06-14-2019